Sulphur dioxide cooperation in hydrolysis reactions of vanadium oxide and hydroxide cluster dianions. (9th February 2018) - Troiani, Anna; Rosi, Marzio; Garzoli, Stefania; Salvitti, Chiara; de Petris, Giulia
Abstract : Gas-phase hydrolysis takes place due to the synergistic action of SO2 and vanadium-containing dianions that succeeds in tightening hydrogen bonds. Abstract : Unprecedented hydrolysis reactions are observed in the gas phase in clusters containing doubly-charged vanadium oxides and hydroxide anions, SO2 and H2 O. The experimental and computational study shows the cooperative effects of the vanadium species, V2 O6 2− and HV3 O9 2−, and sulfur dioxide on the enhancement of the hydrogen bonds of water that allows the acid–base reaction and charge separation in the doubly-charged ion.